The long run effect of taxes on the distribution of top income shares: an empirical investigation - Christoph Gorgas; Christoph A. Schaltegger (Center for Research in Economics, Management and the Arts (CREMA), 2012)
We provide empirical evidence on the impact of personal income taxes and tax competition on income concentration in Switzerland. The fact that Swiss cantons have considerable taxing power enables us to study the effect of differences in the tax burden as well as in the pressure of tax competition on the distribution of top income shares within Switzerland. Using panel regressions covering all 26 Swiss cantons over the years 1917 to 2007 we find substantial evidence that tax competition is a major driving force behind the cantonal tax setting behaviour shaping cantonal income concentration for the very top incomes significantly.
Keywords: 330